An analysis of child sexual grooming legislation in the United States - Kaylor, Leah E. (Psychology, crime & law, 2023)
Both in-person and online sexual grooming of children is a common process used by those who sexually abuse children. Sexual grooming refers to the method by which an adult manipulates a potential minor victim into situations where sexual abuse can more readily take place while at the same time preventing the minor from disclosing the abuse or others recognizing the inappropriate behaviors. Child sexual grooming is considered a precursor to the criminal act of child sexual abuse; however, in some jurisdictions child sexual grooming in and of itself is considered a standalone criminal offense. Both federal and state governments in the United States have created anti-grooming laws to criminalize these preparatory acts to protect children before the sexual abuse can occur. This paper will explore the current research on sexual grooming to provide a framework for understanding sexual grooming behaviors, critically examine federal and state sexual grooming legislation, and provide recommendations on how to evaluate and integrate sexual grooming research into criminal prosecution and policy.